Chronic social defeat induces long-term behavioral depression of aggressive motivation in an invertebrate model system. - Jacqueline Rose; Jan Rillich; Paul A Stevenson (PLoS ONE)
Losing a fight against a conspecific male (social defeat) induces a period of suppressed aggressiveness and general behaviour, often with symptoms common to human psychiatric disorders. Agonistic experience is also discussed as a potential cause of consistent, behavioral differences between individuals (animal "personality"). In non-mammals, however, the impact of single agonistic encounters typically last only hours, but then again studies of repeated intermittent defeat (chronic social defeat) are seldom. We report the effect of chronic social defeat in adult male crickets (Gryllus bimaculatus), for which all known behavioral effects of defeat last only 3 h. Firstly, after 48 h social isolation, crickets that experienced 5 defeats at 24 h intervals against the same, weight-matched opponent exhibited suppressed aggressiveness lasting >24 h, which was still evident when the animals were matched against an unfamiliar opponent at the last trial. Secondly, this longer-term depression of aggression also occurred in 48 h isolated crickets that lost 6 fights at 1 h intervals against unfamiliar opponents at each trial. Thirdly, crickets isolated as larvae until adult maturity (>16 days) were significantly more aggressive, and less variable in their aggressiveness at their very first fight than 48 h isolates, and also significantly more resilient to the effects of chronic social defeat. We conclude that losing an aggressive encounter in crickets has a residual effect, lasting at least 24 h, that accumulates when repeated defeats are experienced, and leads to a prolonged depression of aggressive motivation in subordinates. Furthermore, our data indicate that social interactions between young adults and possibly larvae can have even longer, possibly lifelong influences on subsequent behavior. Social subjugation is thus likely to be a prime determinant of inter-individual behavioral differences in crickets. Our work also opens new avenues for investigating proximate mechanisms underlying depression-like phenomena.